Peer education effectively increases adolescents' knowledge and attitudes in preventing teenage pregnancy - Ratnasari, Desi; Sulistyaningsih, Sulistyaningsih; Anjarwati, Anjarwati (Universitas Aisyiyah Yogyakarta, 2025)
Globally, adolescent births in 2022 were estimated at 1.5 per 1,000 girls, with the highest birth rates in Sub-Saharan Africa (4.6). Adolescent mothers aged 10-19 are at higher risk of developing eclampsia, postpartum endometritis, and systemic infections. Babies born to adolescent mothers are at a higher risk of low birth weight, preterm birth, and severe neonatal conditions (WHO, 2023). In Indonesia, the birth rate in the adolescent age group in 2022 to 26.6% per 1,000 women of reproductive age (WRA) (WHO, 2023). In the Special Region of Yogyakarta, there were 225 cases of adolescent childbirth in 2022. The highest number of adolescent childbirth cases occurred in Sleman Regency with 64 cases, while the lowest was in Yogyakarta City with 25 cases (Dinkes DIY, 2022). This study aims to investigate the effectiveness of peer education in improving knowledge and attitudes among adolescents regarding the prevention of teenage pregnancy. A quasi-experimental design with a control group was used. Sampling was done through purposive sampling with a sample size of 36 respondents per group, calculated using the Lemeshow formula. The questionnaire instrument was tested for validity and reliability. Data analysis was performed using paired sample t-tests and independent sample t-tests. There were significant differences in average knowledge (p-value < 0.001) and attitudes (p-value < 0.001). Logistic regression analysis showed that sources of information and parental education did not affect improvements in adolescents' knowledge and attitudes regarding the prevention of teenage pregnancy.